Myth and Education in School Daily Life - Marcia Reami Pechula; Maria Augusta Hermengarda Wurthmann Ribeiro (Universidade Estadual Paulista Júlio de Mesquita Filho, 2008)
When we speak in myth, we think about the origin of the things; when we speak in daily life, we think about the present of which these things are covered. However, in order to understand, sometimes, expressions used by the people it is necessary to know the narratives that tell us the origin of the world where we live. So, in a modern way, we can say that the myth survives in calendars, in the liturgy, in official ceremonies, tied to the rituals that command such incidents, in the advanced societies in which the man bent under the tecnicism weight and of the mecanicist barbarity, is subjugated by the cruel progress that hems it in and makes it fulfill the paper of wizard's apprentice. So, if our current words are intertwined to the myth, this will also have to be present in the school and in the contents worked by it for what pupils and teachers could understand and update the established relations, along the time, between the historical facts and the narratives that report them. With this objective the Project "To narrate histories, to interchange experiences", financed by UNESP Nucleus of Teaching, was developed in partnership with the Rio Claro General office of Education, in the school "Sérgio Hernani Fittipaldi". There were eleven meetings, in which the art of counting histories, way of knowledge who we are and how we are connected with our similars and with the world around us, was presented to the teachers of Basic Education. While tackling the type fiction, we gave distinction, in the childlike literature, to the myths and its transpositions for the literary narrative. In this form, the first part of this article is constituted by the approach to the conceptual field about the myth. The second part illustrates the literary creations that retake the myths, like the childlike work of Monteiro Lobato.